2015
DOI: 10.1158/1940-6207.capr-14-0403
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Repletion Reduces the Progression of Premalignant Squamous Lesions in the NTCU Lung Squamous Cell Carcinoma Mouse Model

Abstract: The chemopreventive actions of vitamin D were examined in the N-nitroso-tris-chloroethylurea (NTCU) mouse model, a progressive model of lung squamous cell carcinoma (SCC). SWR/J mice were fed a deficient diet (D) containing no vitamin D3, a sufficient diet (S) containing 2000 IU/kg vitamin D3, or the same diets in combination with the active metabolite of vitamin D, calcitriol (C) (80 μg/kg, weekly). The percentage (%) of the mucosal surface of large airways occupied by dysplastic lesions was determined in mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…and suggests that there might be increased nuclear translocation of VDR in MM. On the other hand, murine lung cancer studies have shown that nuclear VDR staining depends on VD sufficiency . Thus, it is possible to hypothesize that these differences between studies in nuclear staining in MM may reflect different VD status among populations living at different latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…and suggests that there might be increased nuclear translocation of VDR in MM. On the other hand, murine lung cancer studies have shown that nuclear VDR staining depends on VD sufficiency . Thus, it is possible to hypothesize that these differences between studies in nuclear staining in MM may reflect different VD status among populations living at different latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-proliferative actions of 25D3 in vitro have been demonstrated in breast, pancreatic and prostate cancer cell lines [ 41 – 43 ]. In vivo , dietary vitamin D3 supplementation protects against cancer development [ 44 49 ] and inhibits outgrowth of human breast and prostate tumor xenografts [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-fixed, paraffin-embedded (FFPE) sections of human PMLs sampled from high-risk subjects undergoing screening for lung cancer were provided by RPCI as part of an IRB-approved study detailed below ( Supplementary Table S3). Dr. Candace Johnson at RPCI provided the FFPE lung sections from the Nnitroso-tris-chloroethylurea (NTCU) mouse model of lung SCC, from SWR/J mice treated with 25 mL of 40 mmol/L NTCU for 25 weeks in accordance with the Institutional Animal Care and Use Committee-approved protocol (41). Briefly, slides were deparaffinized and rehydrated.…”
Section: Immunohistochemistrymentioning
confidence: 99%